2014
DOI: 10.1021/ef501588z
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Microexplosion Occurrence in Water in Diesel Emulsion Droplets during the Leidenfrost Effect

Abstract: Microexplosion phenomenon is attributed for achieving simultaneous reduction of particulate matter and nitrogen oxides in diesel engine exhaust when water in diesel emulsion is used as fuel. In this work, an emulsion droplet suspended on a wire-type thermocouple on a hot plate as the heat source was used to study the evolution of microexplosion phenomenon of emulsions prepared by two different methods. Microexplosion behavior of emulsions produced by a homogenizer and mechanical stirrer with 5, 10, and 20% wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(19 citation statements)
references
References 15 publications
3
16
0
Order By: Relevance
“…Appear the histogram for the emulsions of 5%, 10%, 15%, 20%, and 25% water content. droplets were affected significantly by increasing of water dosage, so the water droplet size was increasing with the increase in water volumetric percentage. This result is in agreement with microscopic result of emulsion for Khan et al (2014). The mean diameter of water dosages: 5%, 10%, 15%, 20% and 25% were 2.2, 3.5, 4.6, 5.2 and 7.7 µm, respectively.…”
Section: The Effect Of Water Dosage On Droplet Size Distributionsupporting
confidence: 91%
“…Appear the histogram for the emulsions of 5%, 10%, 15%, 20%, and 25% water content. droplets were affected significantly by increasing of water dosage, so the water droplet size was increasing with the increase in water volumetric percentage. This result is in agreement with microscopic result of emulsion for Khan et al (2014). The mean diameter of water dosages: 5%, 10%, 15%, 20% and 25% were 2.2, 3.5, 4.6, 5.2 and 7.7 µm, respectively.…”
Section: The Effect Of Water Dosage On Droplet Size Distributionsupporting
confidence: 91%
“…Emulsified fuels are considered as one of the conceivable alternative fuels for reducing the engine exhaust emissions (Abu-Zaid, 2004, Armas et al, 2005, Park et al, 2000 Page 17 of 30 Khan et al, 2014). The most noticeable effects of such fuels are the secondary atomization occurring during the combustion process.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental set-up used in this study was the same as the previous study by Khan et al [29]. A high-speed camera (8001-Phantom Miro M310, Wayne, NJ, USA) coupled with high long distance Microscope-K2 (Boulder, Co, USA), a K-type thermocouple and data logger were synchronized to evaluate the micro-explosion event and record the profile of droplet temperature during the event (Figure 3).…”
Section: Hot Plate Techniquementioning
confidence: 99%
“…Kadota et al [12] used a hot plate to investigate emulsion droplet micro-explosions under Leidenfrost conditions. Khan et al [29] conducted a series of experiments on water emulsified diesel suspended on a thin-wire thermocouple to study the Leidenfrost effect. They conclusively showed that for micro-explosions to occur, large dispersed phase water droplets with faster coalescence rate must exist.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation